1989
DOI: 10.1111/j.1365-2826.1989.tb00117.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Orchidectomy on Nigro‐Striatal Dopaminergic Function: Behavioral and Physiological Evidence

Abstract: In the present experiments, we examined the effect of castration upon two indices of nigro-striatal dopaminergic function in the male rat. In Experiment I, differences in spontaneous locomotor behavioral activity between intact and castrated male rats were examined. The total distance traveled, horizontal activity and mean revolutions of castrated male rats were significantly greater than that of intact males. No significant differences between intact and castrated males were obtained for vertical activity. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
2
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 42 publications
4
14
2
1
Order By: Relevance
“…However, in contrast to our finding, some articles have shown either no effect or an increase in markers of nigrostriatal function (e.g. TH-positive neurons in the SN, striatal dopamine content) following castration (29,30). In these cases, older mice or rats were used for castration.…”
Section: Discussioncontrasting
confidence: 99%
“…However, in contrast to our finding, some articles have shown either no effect or an increase in markers of nigrostriatal function (e.g. TH-positive neurons in the SN, striatal dopamine content) following castration (29,30). In these cases, older mice or rats were used for castration.…”
Section: Discussioncontrasting
confidence: 99%
“…The present experiments show that immunization against GnRH produces a small increase in mesolimbic dopamine and striatal homovanillic acid concentration (table 3) while in other series of experiments it was found that testosterone treatment reduced in vitro dopamine release [6], All these experiments agree well with the suggestion that testosterone tends to reduce the activity of mesolimbic or nigro striatal dopaminergic systems.…”
Section: Discussionsupporting
confidence: 80%
“…It has been known for many years that brain catecholamines have stimulatory effects on male sexual behavior [1][2][3] and that testosterone attenuates some behavioral responses that are me diated by dopamine [4,5], In agreement with these findings, it has been recently shown that testosterone also decreases dopa mine striatal release [6], In addition, brain 5-hydroxytryptamine has been implicated in the regulation of male sexual behavior, as suggested by the finding that synthesis blockade increases rat mounting behavior, an effect that is counteracted by 5-hydroxytryptophan administration [7][8][9].…”
supporting
confidence: 71%
“…As sex hormones exert unique organizational effects on brain and evolving behavior during adolescence, it is important to study this developmental period. Preclinical studies in mostly adult male rats report that testosterone can both increase (de Souza Silva et al, 2009;Thiblin et al, 1999) and decrease (Beatty et al, 1982;Dluzen and Ramirez, 1989;Forgie and Stewart, 1994;Menniti and Baum, 1981) striatal dopamine activity. Testosterone treatment increased dopamine turnover but not dopamine synthesis in the striatum of adult male rats (Thiblin et al, 1999) and…”
Section: Accepted Manuscriptmentioning
confidence: 98%